Modular Distance Learning in the New Normal: Challenges on its Implementation - Acut Junpel (Hasanuddin University, 2023)
This basic research was conducted to determine the challenges of teachers in the implementation of modular distance learning in the new normal of the public elementary and secondary schools in the District of Gitagum, Division of Misamis Oriental. Specifically, it sought to: a) describe the characteristics of the respondents; b) determine the challenges encountered by the teachers in terms of accessibility, availability of resources, support to learners, teachers’ competence and teaching strategies, assessment, and health and safety measures; c) determine the significant relationship between the respondents’ challenges and their characteristics; and d) come up with an intervention plan based on the results of the study. The respondents of the study were the one hundred five (144) public school teachers in the District of Gitagum, Division of Misamis Oriental. A researcher-made survey questionnaire was employed to obtain specific information about the study. The data were analyzed using descriptive statistics such as frequency counting of data, percentage, mean and standard deviation. Pearson Product Moment of Correlation was employed to test the significant relationship between the respondent’s challenges and their characteristics. An intervention plan was designed to help teachers in finding solutions to the challenges they are facing in the implementation of modular distance learning. The teachers’ challenges were low in the implementation of modular distance learning. It suggests that teachers faced few challenges or that the challenges they encountered were of low intensity. In other words, it implies that teachers found it relatively manageable to implement modular distance learning, and the difficulties they encountered were not severe. Teachers’ challenges were significant to sex, position, teaching experience and attitudes towards modular distance learning in the new normal. It is recommended that teachers seek support from stakeholders and the local government to acquire funds for better implementation.